Discovery and Characterization of a Novel Bipartite Botrexvirus From the Phytopathogenic Fungus Botryosphaeria dothidea - Yang, Mengmeng; Xu, Wenxing; Zhou, Xiaoqi; Yang, Zuokun; Wang, Yanxiang; Xiao, Feng; Guo, Yashuang; Hong, Ni; Wang, Guoping (Frontiers in Microbiology, 2021)
In this study, we described a novel +ssRNA mycovirus, named Botryosphaeria dothidea botrexvirus 1 (BdBV1), from a phytopathogenetic fungus Botryosphaeria dothidea showing abnormal morphologies and attenuated virulence. BdBV1 is phylogenetically related to Botrytis virus X (BotVX) as the second member under the newly built genus Botrexvirus of the family Alphaflexiviridae, but comprises two ssRNA segments (RNA1 and RNA2 with the lengths of 5035 and 1063 nt, respectively). The RNA1 and RNA2 encode putative replicase and coat proteins (CP) sharing high identities with the corresponding ones of both fungal and plant viruses, respectively. Moreover, open reading frames (ORF) 2 to 4 of RNA1 shared no detectable identities with known viral proteins. Immunosorbent electron microscopy (ISEM) analysis revealed BdBV1 encapsidated in filamentous particles using the antibody triggered by in vitro expressed CP. Biological test for BdBV1-infected and -free strains revealed that BdBV1 is probably related to the impaired biological traits of the host strain. This study presents a novel bipartite botrexvirus which closely related to fungal and plant viruses and also mono- and multi-partite viruses and contributes useful information to better understand the virus evolution.